2016
DOI: 10.7205/milmed-d-15-00037
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Brief Measure of Psychological Resilience: An Adaptation of the Response to Stressful Experiences Scale

Abstract: Resilience helps determine how people respond to stress. The Response to Stressful Events Scale (RSES) is an existing 22-item measure of resilience. We investigate the psychometric properties of the RSES and develop a 4-item measure of resilience using the most discriminating items from the RSES. Among two samples of military personnel presenting to mental health clinics, we see that the abbreviated resilience measure displays comparable internal consistency and test-retest reliability (versus the existing RSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 28 publications
2
23
1
Order By: Relevance
“…The psychometric surveys were administered before the course, on day 3 and on conclusion on day 6 to assess changes in attitudes, resilience, cohesion, and stress-related psychological variables. The survey questions (online supplementary table 2) were based on published normative scales 15–21. Analyses conducted on the entire sample showed statistically significant increases in combat and unit readiness, unit and vertical cohesion, and team communication and leadership quality.…”
Section: Discussionmentioning
confidence: 99%
“…The psychometric surveys were administered before the course, on day 3 and on conclusion on day 6 to assess changes in attitudes, resilience, cohesion, and stress-related psychological variables. The survey questions (online supplementary table 2) were based on published normative scales 15–21. Analyses conducted on the entire sample showed statistically significant increases in combat and unit readiness, unit and vertical cohesion, and team communication and leadership quality.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience to the most stressful events experienced by participants is measured by the 4-item Response to Stressful Events Scale (RSES-4; [51]. The RSES-4 is a brief self-report resilience measure that was developed from the 22-item Response to Stressful Events Scale (RSES-22; [52].…”
Section: Design and Methodsmentioning
confidence: 99%
“…The RSES-4 is a brief self-report resilience measure that was developed from the 22-item Response to Stressful Events Scale (RSES-22; [52]. Construct validity is supported by a strong correlation with the RSES-22 ( r = 0.90), as well as acceptable correlations ( r = 0.29–0.39) with measures of burnout and distress [51].…”
Section: Design and Methodsmentioning
confidence: 99%
“…Scholars from many disciplines including nursing have utilized quantitative screening tools to establish the presence or absence of resilience (De La Rosa, Webb-Murphy, & Johnston, 2016;Dodd, Driver, Warren, Riggs, & Clark, 2015;Hemington et al, 2017;Jeste et al, 2013;Mache, Vitzthum, Wanke, Klapp, & Danzer, 2014;McKibbin et al, 2016;Scoloveno, 2015) Scale. The pillars of the resilience research community identified resilience as an adaptive life process (Bonanno, 2004;Garmezy, 1971;Masten, 2001;Ungar, 2004).…”
Section: Hardiness Strengthens the Ability To Harness Resourcesmentioning
confidence: 99%